E-sport tokom pandemije Covid-19 i njegov negativan uticaj na zdravlje dece - Milic, M. K. (Sports Science and Health, 2020)
The Covid-19 virus pandemic has brought many problems, both in the functioning of everyday life and in various spheres of human health. Sport has always been considered a synonym for a healthy physical and mental state of people. The emergence of the phenomenon of e-sports has brought agility to a new market that cannot be defined by physical culture. The research will explain and prove the negative effects on children`s health based on a survey whose results prove that most of the surveyed children engage in e-sports activities during a pandemic, rather than physical exercise, as well as other relevant research. Considering that sport in general and e-sport as a newly formed occupation, mostly children, have no other than terminological similarities, the research topic is subject to critical evaluation.